Quality management and labor productivity of formal companies in Perú: A non-experimental design and causal machine learning techniques; Gestión de calidad y productividad laboral de las empresas en el Perú: Un dise\~no no experimental y técnicas de machine learning causal - Mario D. Tello; Daniel S. Tello Trillo (Estudios de Economía, 2024)
This paper evaluates the impacts of quality management tools on the labor productivity of companies in Peru for the period 2014-2019 based on causal Machine Learning (ML) techniques (MLC), which reduce or eliminate three potential problems: the endogeneity of the variables of interest, the existence of confusing variables (confounding) and overfitting due to the introduction of many control variables. Using the National Survey of Companies (INEI-ENE 2023), the evaluation indicates that quality control tools affect the productivity of formal companies, particularly large and medium-sized companies.
Keywords: J24; L15; P42; 330; Labor Productivity; Quality Management; Machine Learning